2003
DOI: 10.1046/j.1538-7836.2003.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+ T-cell epitope repertoire on the C2 domain of coagulation factor VIII

Abstract: Summary.  Approximately 25% of severe hemophilia A patients develop antibodies (Ab) that neutralize the procoagulant function of factor (F)VIII (inhibitors). Autoimmune FVIII inhibitors may develop in individuals without congenital FVIII deficiency and cause acquired hemophilia. Low titers of anti‐FVIII Ab may be present in hemophilia A patients without inhibitors and in healthy blood donors. FVIII‐specific CD4+ T‐cells drive the synthesis of anti‐FVIII Ab. We examined the epitope repertoire of CD4+ T‐cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 57 publications
2
101
1
1
Order By: Relevance
“…The A2, A3, and C2 domains of FVIII participate in vWF (9-13), LRP (14,15), and phospholipid binding (16)(17)(18)(19)(20) that contributes to catabolism of FVIII, and these domains also contain epitopes that can lead to inhibitor development (24)(25)(26). Therefore, it will be of interest to investigate the influence of macromolecular interactions on catabolism and immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The A2, A3, and C2 domains of FVIII participate in vWF (9-13), LRP (14,15), and phospholipid binding (16)(17)(18)(19)(20) that contributes to catabolism of FVIII, and these domains also contain epitopes that can lead to inhibitor development (24)(25)(26). Therefore, it will be of interest to investigate the influence of macromolecular interactions on catabolism and immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, we speculate that the PI reduces FVIII immunogenicity by multiple mechanisms. Anti-FVIII antibodies targeted against epitopes in A2, A3, and C2 domains of FVIII (24)(25)(26). As the lipid binding involve these domains, these immunogenic epitopes were shielded resulting in reduction of antibody titer levels by immune ignorance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoprecipitation and inhibitor neutralization assays of the inhibitor plasma from hemophilia A patients clearly indicated that the anti-light chain antibody titer was the highest (12). More recently, Reding et al (13) and Pratt et al (14) have identified several universal epitopes for CD4ϩ T-cells in the 2291-2330 region of the C2 domain using proliferation assays with CD4ϩ cells from normal humans, hemophilia A patients (13), and mice (14). Three-dimensional models proposed based on crystallographic studies and mutational analysis show that the C2 domain also contains 2-4 hydrophobic loops and other charged residues that promote lipid binding ( Fig.…”
mentioning
confidence: 97%
“…9 Os inibidores do FVIII são imunoglobulinas policlonais principalmente da subclasse IgG4, cuja síntese é direcionada por células T CD4+ específicas para o FVIII. 10 Entretanto, subclasses IgG1 e IgG2 estão também usualmente presentes nas populações de anticorpos anti-FVIII. Estes dados sugerem que os inibidores do FVIII estão associados com uma combinação de respostas Th1/Th2.…”
Section: Imunobiologia Dos Inibidores Do Fator VIIIunclassified